Analisis Seven Tools Pada Pengendalian Kualitas Proses Vulkanisir Ban 1000 Ring 20 di CV Citra Buana Mandiri Surabaya - Andrianto Eko Saputra; Nina Aini Mahbubah (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
CV. Citra Buana Mandiri is a service enterprise  which provide service such as retreading of used tires. During  retread production process, there were found defects which caused by external and internal factors so the final product  are not in accordance with the quality standards set by the firm.   The purpose of this research is to identify the causes of ring 20 tire defects, analyze whether the product defects are still within control limits and provide recommendations for improvements to improve the quality of ring 20 tires. Tseven tools was used as research approach with final result as follows: identifying factors that cause 1000 tire defects.  ring 20 is the factor of human, machine, raw material, environment and method, then we get 13 possible root causes of the problem.  The proportion of defects in the 1000 ring 20 tire product, it can be concluded that the product is still within control limits, but based on the company's standard tolerance, the percentage of defects that are still outside the predetermined standard is 1 percent and 13 improvement along production stages in order to maintaining excellent quality.